ANALISIS PENGARUH WORKING CAPITAL TURNOVER TERHADAP LIKUIDITAS DAN PROFITABILITAS - Minar Savitri, Dhian Andanarini (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2014)
This study aimed to assess the influence of WCT towardprofitability and liquidity of manufacturing companies in IndonesiaStock Exchange.The population of this research is everymanufacturing company enlisted in the BEI at the year 2009-2012.The samples were obtained by using the purposive sampling methoduntil only 15 companies were qualified as samples. This research usedregression analysis method to find out the effect of independentvariables, which are wct to the profitability and liquidity of thecompany.The result of this research shows that the WCT (workingcapital turnover) has insignificant effect to the profitability andliquidity of manufacturing companies enlisted in the BEI at year 2005-2012